Impact of the COVID-19 pandemic on dental practice in Serbia - prospective study - Ivanjac Filip; Konstantinović Vitomir; Miličić Biljana (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction/Objective. The COVID-19, pandemic had a great impact on all spheres of dental practice. Dentists are the most affected category, due to their line of work. Studies conducted worldwide have shown a range of repercussions in dentistry including lockdowns, limited access to dental services, changes in prices, working hours and availability of protective equipment, increased anxiety levels, changes in the protocols, and personnel fear of contracting the disease at work. The aim of this prospective observational survey study was to evaluate the impact of the COVID-19 pandemic on the dental practices in Serbia, as well as the challenges and consequences faced by dentists since the beginning of the pandemic, via an anonymous questionnaire. Methods. Multi layered questioner was used divided in to four sections: 1. Demographic; 2. Dental office professional experience; 3. Epidemiological professional experience; 4. Personal pandemic experience. Results. In total, 459 members of the Serbian Dental Chamber participated, gender distribution was 34.4% men and 65.6% women, age range was 26–81 years, of which 76.4% were immunized against COVID-19. Professional, epidemiological and personal experience showed high level of preventive measures, overcoming professional limitations in order to lower the probability of contracting and spreading the disease. Conclusion. The COVID-19 pandemic had a large influence on the dental practice in Serbia. Many dentists had to overcome the professional, economic and personal limits. The immunization made all the difference and created a safer environment for dentists and patients.